PEMBERLAKUAN CLINICAL PATHWAY DALAM PEMBERIAN LAYANAN KESEHATAN DAN AKIBAT HUKUMNYA - Yohanes Firmansyah; Gunawan Widjaja (Cross-border, 2022)
In today's modern era, hospitals as part of health services require an internal regulation based on law, otherwise known as hospital by laws. One form of implementation of hospital by laws is the implementation of clinical pathways, which become a reference or standard for medical services from the time the patient arrives until the patient leaves the hospital. This research is descriptive-analytical-explorative research with a statutory approach. The data used in this study is secondary data, which consists of primary, secondary, and tertiary legal materials. The results of this study discuss a clinical pathway that describes a method or instrument used in providing care to patients by all health and medical personnel at the hospital. Clinical pathways have been shown to reduce unnecessary variation in patient care, reduce discharge delays through more efficient discharge planning, and increase the cost-effectiveness of clinical services. The approach and goals of the clinical pathway are consistent with total quality management and continuous quality improvement and are essentially the application of these principles at the patient's bedside. This article investigates the increasing use of clinical pathways, their benefits to healthcare organizations, their use as a tool for continuous quality improvement activities directly related to patient care, and the medico-legal implications involved.